Development and applications of transparent conductive nanocellulose paper. Issue 1 (31st December 2017) - Li, Shaohui; Lee, Pooi See
Abstract: Increasing attention has been paid to the next generation of 'green' electronic devices based on renewable nanocellulose, owing to its low roughness, good thermal stability and excellent optical properties. Various proof-of-concept transparent nanopaper-based electronic devices have been fabricated; these devices exhibit excellent flexibility, bendability and even foldability. In this review, we summarize the recent progress of transparent nanopaper that uses different types of nanocellulose, including pure nanocellulose paper and composite nanocellulose paper. The latest development of transparent and flexible nanopaper electronic devices are illustrated, such as electrochromic devices, touch sensors, solar cells and transistors. Finally, we discuss the advantages of transparent nanopaper compared to conventional flexible plastic substrate and the existing challenges to be tackled in order to realize this promising potential. Abstract :